Polski ośrodek rządowy o przeszłości i przyszłości międzynarodowej organizacji bezpieczeństwa (1939-1945) - Ponczek, Eugeniusz (Acta Universitatis Lodziensis. Folia Historica, 1999)
This article deals with the attitude of the Polish Government in exile during the Second World War and his representation in Poland towards the idea of creation an international security organisation which would be able to maintain a democratic and peaceful order in the post-war world. That idea was compared to the „Versatile order” after the First World War and the activity of the League of Nations. The necessity to win the war against both German and Soviet aggressors was firmly stressed but „to win the peace” seemed even more important. The Polish experts took up wide spread work on preparation the future treaty with Germany. Their attitude towards the political order between the wars and activity of the League of Nations was rather critical. According to their opinion that organisation had not been able to give the guarantee of security for the European countries, because of insufficient efficacy of its activity and limited capability to oppose against pro-war tendencies. Basing on those experiences they proposed to create new and better international security organisation after the war which would be convenient to the hopes of Polish society demanding restitution of an independent, sovereign, „whole” from the territorial point of view (included all the pre-war Polish east provinces and demanded aggrandisement on the west) and democratic Poland. Such a state should become an important factor of the stability and peace in Central and East Europe. Polish government in exile strongly opposed the very idea of the spheres of influences in Europe as being contrary to the declaration of the Atlantic Charter. The members of the future international security organisation could not accept such a project. At the end of the Second World War Polish authorities protested against the decision not to invite Polish delegation to the Conference in San Francisco, where the United Nations were to be created. It was considered from the moral point of view. In the same time when the Conference in San Francisco approached to its end, sixteen of the leaders of Polish underground state were on trail in Moscow while on Stalin’s influence „The Temporary Government of National Unity” dominated by the Polish communist wad proclaimed as the only legal one in Poland. All those events were notified with bitterness by the Polish government in exile and patriotic opinion in the country suffering under Soviet rule.